The Duration of Hemodialysis Treatment and the Adherence of Chronic Kidney Disease Patients in Fluid Intake Limitation: a Relationship - Mailani, Fitri; Bakri, Sri Olta (Caring: Indonesian Journal of Nursing Science, 2020)
Hemodialysis is a routine medical intervention for a patient with chronic kidney disease. The duration of hemodialysis treatment makes the patient's behavior change to be not adherence to the recommended diet, including restrictions on fluid intake. The objective of this research is to determine the Relationship duration of hemodialysis treatment with Adherence to fluid restriction of Chronic Kidney Disease Patients. This cross-sectional study involving 44 respondents, taken by consecutive sampling techniques. Research has been conducted in the hemodialysis room at the Reksodiwiryo hospital in Padang from May-June 2019. Data collection was carried out by looking at medical records and questionnaires regarding fluid intake compliance in patients with chronic kidney disease. The data obtained were analyzed univariate with frequency distribution and bivariate with the Kendall Tau test. The results showed that there were 26 (59.1%) non-adherence patients, and 18 (40.9%) patients were adherence to limiting fluid intake. Old patients were 17 people (38.6%) and new patients were 27 (61.4%). The Kendall Tau bivariate test showed that the length of hemodialysis has a significant correlation with adherence fluid restriction (p = 0.014), with a negative correlation (r -0.375), it's meaning that the longer the hemodialysis, the lower the fluid restriction compliance. It is expected that hemodialysis nurses regularly evaluate the compliance of hemodialysis patients and routinely carry out educational and motivational programs as well as fluid diet counseling at each hemodialysis session. Keywords: compliance, fluid, hemodialysis, restriction